Analisis Monitoring Evaluasi Terhadap Kejadian Stunting Di Puskesmas Simpang Rimba Bangka Selatan : Evaluation Monitoring Analysis of Stunting Incidents at Simpang Rimba Community Health Center, South Bangka - Nurlita, Asta Bella (Dohara POAJ, 2024)
Introduction: One of the nutritional problems faced by Indonesia is the incidence of short toddlers (stunting). Stunting is very important because it will affect human resources in the future. Stunted toddlers are easily infected with diseases and can suffer from degenerative diseases as adults. Stunting is an event characterized by short stature due to chronic malnutrition, as well as a child's appetite pattern which results in poor nutritional status. The purpose of this study was to determine the effect of nutritional evaluation monitoring on the incidence of stunting at the Simpang Rimba Health Center in South Bangka in 2023. Methods: In this study, the authors used the type Qualitative research is a research method used to research natural objects where the researcher is the key instrument, data collection techniques are carried out by triangulation, data analysis is inductive, and qualitative research emphasizes meaning rather than generalization. Results: The results of this study indicate that there is an effect of nutritional evaluation monitoring on the incidence of stunting at the Simpang Rimba Health Center, South Bangka in 2023 based on timeliness. There is an influence of nutritional evaluation monitoring on the incidence of stunting at the Simpang Rimba Health Center in South Bangka in 2023 based on resource utilization and costs. Discussion: This study concludes that there is an effect of nutritional evaluation monitoring on the incidence of stunting at the Simpang Rimba Health Center in South Bangka in 2023 based on timeliness, cycle time, resource utilization, and costs. After that, it can be suggested that it is hoped that the Simpang Rimba Health Center will remain consistent in dealing with existing malnutrition and be more persistent in doing work so that all the goals to be achieved can run optimally.